Advance membrane technology for biomass separation - Mohammad Faiz Farhan Bin Abdul Rahim (Nanyang Technological University, 2023)
The increasing worldwide need for protein is expected to elevate the significance of single cell protein (SCP) or microbial protein as a novel and significant player in the market. Microbial protein recovered from biomass is considered a potentially superior product that is anticipated to alleviate the possible shortage of protein in the future. Microbial biomass cultivated in bioreactors are generally diluted, with solid content of effluent typically less than 2% by mass. It’s important to concentrate biomass to high solid content for further protein recovery. There are many techniques available for biomass separation and concentration, such as centrifugation, flotation, coagulation/flocculation, and membrane technology. Among these techniques, membrane technology is promising due to various advantages. These advantages include continuous separation under mild conditions, low energy requirement, small footprint and no addition of chemicals allowing high quality biomass. As such this study aims: (1) to investigate the feasibility of concentrating different types of biomasses using the low-pressure hollow fibre ceramic membrane. Specifically, suspensions of three types of biomasses were tested; namely purple phototrophic bacteria (PPB), aerobic heterotrophic bacteria (AHB) and algae; (2) to investigate the fouling mechanisms of ceramic membrane during biomass concentration; (3) to develop effective fouling control strategies for sustainable long-term membrane system operation for biomass concentration. Results suggested that membrane technology is promising in biomass concentration as it requires a short amount of time for the concentration of biomass and does not require the addition of any chemicals. The membrane separation was successfully to concentrate different types of biomasses with CF ranging from 1.6-6.7. For AHB biomass concentration, the treatment capacity was around 3.5-5 L/hr for one ceramic MF membrane module, which provided the guideline for the design of the pilot-scale biomass concentration system. The treatment capacity was around 2.5-3 L/hr for PPB biomass concentration, and 4.28-6.67 L/hr for algae using one ceramic MF membrane module. During biomass separation, the main fouling mechanism was the cake layer formation on ceramic membrane surface. Periodic backwashing was effective for membrane fouling control to remove cake layer during biomass harvest. Furthermore, different chemical cleaning protocols were developed for different types of biomasses for sustainable long-term operation. For PPB biomass, chemical cleaning with 2 g/L NaOH+0.2% citric acid could restore the flux to 97%, while 0.1% NaClO+0.2% citric acid cleaning was effective to recover up to 85% for fouled membrane by AHB biomass. For fouled membrane by algae, 63% flux recovery was achieved after chemical cleaning with 2 g/L NaOH+0.2% citric acid. In summary, the ceramic multibore membrane was feasible to apply in biomass concentrating process.